FAKTOR PENGHAMBAT PENERAPAN GOOD MANUFACTURING PRACTICES PADA PROSES PENGENDALIAN KUALITAS BANDREK DI CV. X - sarah jasmine latief; Lucyana Trimo (AGROINTEK, 2019)
Along with the increasing production of food and beverage industry in Indonesia, people today insist for hygienic food product. CV. X is an Industry that produces instant drinks. However, CV. X has not implemented Good Manufacturing Practices on the quality control of its products. There are employees who have not complied with the regulations while working and the machine has been damage several times, so it inhibit the production process. As a result, there are product defects resulting in as much as 5% of total production. The design used in this research is qualitative with case study techniques. The analysis techniques used in this research is descriptive analysis techniques with tool named fishbone diagram. The result showed that 72% of GMP aspects had been fulfilled but 28% had not been so the implementation of GMP was hampered. According to fishbone diagram result,there are four the inhibiting factor that have been identified.